(untitled) (Journal of Engineering, 2022)
A fixed firefighting system is a key component of fire safeguarding and reducing fire danger. It is installed as a permanent component in a structure to protect the entire or a portion of the building and its contents. The study aims to review the previous studies that deal with the evaluation of fire safety measures and their use in resolving problems associated with fire threats in buildings. For this reason, a number of previous studies in this field were reviewed compared with the NFPA code. The findings revealed that regulatory developments over the last several decades had created an atmosphere conducive to innovation. This has resulted in a growth in the number of fixed firefighting system types now obtainable. These solutions provide substantial distinction in terms of performance and hence safety. Not only is the availability of different fire risk alleviation systems important, but so is the election of the most convenient solution for the job. This is typically seen inside regulatory procedures and basics of thumb or heuristics and depends on the knowledge and expertise of divergent specialists. When several perceived danger and results thresholds are surpassed, fixed firefighting systems are frequently included as extra fire protection and resilience measures